Antioxidant Capacity with Physical Property Variations of Morinda citrifolia L. Juice in Traditional Fermentation - Malsha H. Samarasiri; Thushitha A. Chandrasiri; Diunuge B. Wijesinghe; Sanja P. Gunawardena (Chemistry Proceedings, 2022)
This study determined the physical property variations during the traditional fermentation of Morinda citrifolia L. (noni) juice and their correlations to antioxidant capacity were identified. The temperature and pH of the juice, temperature, and humidity within the fermenter and juice volume were monitored. Both temperatures were within the range of 29.5–33 °C. The pH of the juice decreased from 3.98 to 3.23. The humidity increased rapidly from 98.95% to 99.90%. The maximum juice volume was about 1.37 L. The maximum antioxidant capacity was around 84% of the DPPH scavenging activity. Therefore, the physical property variations cannot be correlated significantly to the antioxidant capacity of noni juice.